Maintaining Upright Posture during Visual Control of the Common Center of Pressure in Different Standing Conditions - Kazennikov, O. V.; Shlykov, V. Yu; Levik, Yu. S. (Human physiology, 2025)
The movement of the common center of pressure (CCP) and center of pressure (CP) of the right and left legs of a subject standing on two force platforms was studied. In the first variant, with passive visual feedback, the subject fixed his gaze on the intersection of two lines; in the second variant, with active feedback, the subject, changing his posture, had to keep the cursor position on the monitor at the intersection, reflecting the position of the CCP. In both variants of the experiment, the body weight was either symmetrically distributed between the legs or partially transferred to the right or left leg. The effect of different types of visual feedback on the standard deviation of the position and on the speed of movement of the CCP and CP of each leg was compared. When standing with a symmetrical load on both legs, active visual feedback on the position of the CCP led to a decrease in the standard deviation of the position of the CCP and CP of each leg. After transferring the body weight to one leg, the presence of active visual feedback did not affect the value of the standard deviation of the CCP and CP of each leg. Probably, the equilibrium position of the body, determined on the basis of afferentation from the loaded leg, corresponded to the position specified by visual feedback. Under conditions of active visual feedback, the speed of the CP movement increased in all variants of weight distribution. The change in the speed of the CP movement of the leg depended on the load on it. With a symmetrical load, the speed of the CP movement of the left leg increased. With an asymmetrical load, the speed of the CP movement of the loaded leg increased. It can be assumed that the equilibrium position of the body was determined mainly on the basis of afferentation from the leg involved in maintaining stability. When standing with a symmetrical weight distribution, afferentation from the dominant leg is more significant for determining the body position, so it was important to maintain the position of the dominant leg. In conditions with an asymmetrical weight distribution, the loaded leg is more involved in postural control, and tracking the visual position of the CP was performed by the unloaded leg. It is assumed that in order to develop a reference body position and maintain an upright posture, it was necessary to maintain a stationary CP position of the leg that was mainly involved in maintaining the upright posture.